2014
DOI: 10.3184/095422914x14047407349335
|View full text |Cite
|
Sign up to set email alerts
|

Mycoremediation (bioremediation with fungi) – growing mushrooms to clean the earth

Abstract: Some of the prospects of using fungi, principally white-rot fungi, for cleaning contaminated land are surveyed. That whiterot fungi are so effective in degrading a wide range of organic molecules is due to their release of extra-cellular ligninmodifying enzymes, with a low substrate-specificity, so they can act upon various molecules that are broadly similar to lignin. The enzymes present in the system employed for degrading lignin include lignin-peroxidase (LiP), manganese peroxidase (MnP), various H 2 O 2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(49 citation statements)
references
References 11 publications
(16 reference statements)
0
45
0
4
Order By: Relevance
“…129 The effect of inoculation of soil microcosms with T. versicolor and P. chrysosporium on wood chips on differential degradation of pesticides (simazine, trifluralin and dieldrin, 10 mg kg −1 soil) at two water potentials (−0.7 and −2.8 MPa, at 15 °C) was studied through soil microcosms destructively sampled after 6/12 weeks for determination of four extracellular enzymes, respiration and content of the pesticides. 158 It was found that fungal treatments increased extracellular enzymes cellulase/dehydrogenase and laccase (mainly with T. versicolor), respiratory activity and degradation of the three pesticides by wood chip addition alone (20-30%) in inoculated soil containing higher contents of pesticide mixtures. T. versicolor increased degradation of simazine (27-46%), trifluralin (5-17%) and dieldrin (5-11%) after 12 weeks and P. chrysosporium by 34-48%, 0-30% and 40-46%, respectively, when compared with controls, even at −2.8 MPa water potential, suggesting that effective bioremediation of xenobiotic mixtures using wood chips and fungal inoculants is achievable over a relatively wide water potential range when compared with that allowing plant growth (−1.4 MPa).…”
Section: Mycoremediationmentioning
confidence: 99%
See 4 more Smart Citations
“…129 The effect of inoculation of soil microcosms with T. versicolor and P. chrysosporium on wood chips on differential degradation of pesticides (simazine, trifluralin and dieldrin, 10 mg kg −1 soil) at two water potentials (−0.7 and −2.8 MPa, at 15 °C) was studied through soil microcosms destructively sampled after 6/12 weeks for determination of four extracellular enzymes, respiration and content of the pesticides. 158 It was found that fungal treatments increased extracellular enzymes cellulase/dehydrogenase and laccase (mainly with T. versicolor), respiratory activity and degradation of the three pesticides by wood chip addition alone (20-30%) in inoculated soil containing higher contents of pesticide mixtures. T. versicolor increased degradation of simazine (27-46%), trifluralin (5-17%) and dieldrin (5-11%) after 12 weeks and P. chrysosporium by 34-48%, 0-30% and 40-46%, respectively, when compared with controls, even at −2.8 MPa water potential, suggesting that effective bioremediation of xenobiotic mixtures using wood chips and fungal inoculants is achievable over a relatively wide water potential range when compared with that allowing plant growth (−1.4 MPa).…”
Section: Mycoremediationmentioning
confidence: 99%
“…Such preparation methods enhance the likelihood of success in the first phase. 158 The are many studies using mycoremediation in artificially contaminated sites spiked with organic pollutants, but the importance of researches under nonsterile conditions, with real contaminated soils/effluents, became more common in the last twenty years and made their results potentially transferable to a field scale, using biostimulation, bioaugmentation or, more recently, both technologies. This process depends on nutrient availability and the optimum presence of other factors that support biological functions, such as the concentration of the contaminants and their bioavailability, site characteristics, moisture, temperature, redox potential and oxygen content.…”
Section: Mycoremediationmentioning
confidence: 99%
See 3 more Smart Citations